2016
DOI: 10.18632/oncotarget.9176
|View full text |Cite
|
Sign up to set email alerts
|

Environmental tobacco smoke increases autophagic effects but decreases longevity associated with Sirt-1 protein expression in young C57BL mice hearts

Abstract: Recently, a survey by the Centers for Disease Control and Prevention (CDC) reported that nearly 90% of U.S. adult smokers began smoking at the age of 18. This demonstrates that the exposure to environmental tobacco smoke (ETS) of youngsters today is changing from passive smoking to active smoking (direct inhalation of tobacco). In the current study, an investigation of ETS exposure in young C57BL mice was conducted. After 6 weeks of ETS exposure, the Sirt-1 protein level was decreased and cardiac autophagy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The mammalian genome encodes 7 sirtuin isoforms (SIRT 1 to SIRT7) that vary in their tissue specificity, subcellular localization, enzymatic activity, and targets [ 22 , 24 25 ]. SIRT6 is a chromatin-associated enzyme involved in deacetylating histone 3 at Lys9 (H3K9) and H3K56, thereby regulating gene expression, cellular metabolism, and the inflammatory response [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian genome encodes 7 sirtuin isoforms (SIRT 1 to SIRT7) that vary in their tissue specificity, subcellular localization, enzymatic activity, and targets [ 22 , 24 25 ]. SIRT6 is a chromatin-associated enzyme involved in deacetylating histone 3 at Lys9 (H3K9) and H3K56, thereby regulating gene expression, cellular metabolism, and the inflammatory response [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another term that showed significant occurrence was SIRT-1. Many studies attribute the biological properties of resveratrol to its ability to activate this SIRT-1 [68,[82][83][84], an enzyme classified as an NAD+ dependent histone deacetylase, involved in metabolic processes, cellular stress regulation, and longevity [85,86]. In one study, the researchers demonstrated that the activation of SIRT1 by resveratrol (30 mg/kg/day for 8 weeks) reduced Tau protein phosphorylation induced by streptozotocin injection into the brain, confirming its protective role [87].…”
Section: Discussionmentioning
confidence: 96%